The human microbiome in disease and pathology. Issue 12 (6th May 2022) - Manos, Jim
Abstract : This narrative review seeks to examine the relationships between bacterial microbiomes and infectious disease. This is achieved by detailing how different human host microbiomes develop and function, from the earliest infant acquisitions of maternal and environmental species through to the full development of microbiomes by adulthood. Communication between bacterial species or communities of species within and outside of the microbiome is a factor in both maintenance of homeostasis and management of threats from the external environment. Dysbiosis of this homeostasis is key to understanding the development of disease states. Several microbiomes and the microbiota within are used as prime examples of how changes in species composition, particularly at the phylum level, leads to such diverse conditions as inflammatory bowel disease (IBD), type 2 diabetes, psoriasis, Parkinson's disease, reflux oesophagitis and others. The review examines spatial relationships between microbiomes to understand how dysbiosis in the gut microbiome in particular can influence diseases in distant host sites via routes such as the gut–lung, gut–skin and gut–brain axes. Microbiome interaction with host processes such as adaptive immunity is increasingly identified as critical to developing the capacity of the immune system to react to pathogens. Dysbiosis of essential bacteria involved in modification of host substrates such as bile acid components can result in development of Crohn's disease, small intestine bacterial overgrowth, hepatic cancer and obesity. Interactions between microbiomes in distantly located sites are being increasingly being identified, resulting in a 'whole of body' effect by the combined host microbiome.